Reduction of NOx and SO2 Emissions by Shore Power Adoption - Duy-Hieu Nguyen; Chitsan Lin; Nicholas Kiprotich Cheruiyot; Jen-Yu Hsu; Ming-Yuan Cho; Shih-Hsien Hsu; Chin-Ko Yeh (Aerosol and Air Quality Research)
Abstract Shore power systems, an alternative energy source to ships at berth, have the potential to improve air quality at ports and surrounding areas. This study assessed the reduction of four major air pollutants: PM10, PM2.5, NOx, and SO2, from adopting shore power at the Port of Kaohsiung. The reduction was assessed in two scenarios, S1 and S2, with a capacity to provide shore power to 342 and 780 ships at berth, respectively. The emissions from the ships were estimated based on the operation loads of the auxiliary engines, average time at berth, and emission factors. Additionally, the AERMOD model was used to simulate the ground-level dispersion of the four pollutants to the surrounding urban areas. The simulation results showed that the elevated areas in the city were vulnerable to ship emissions, especially for NOx. The maximum simulated contribution at ground level from S1 and S2 were 78.8 µg m−3 and 147 µg m−3 for NOx, and 20.1 µg m−3 and 42.5 µg m−3 for SO2, respectively; while the results for PM10 and PM2.5 were insignificant. The reduction benefit was then calculated as the ratio of the simulated air pollutant concentration to the observed concentration at the local air quality monitoring station. The highest reduction benefit of shore power adoption at the port was for NOx and SO2 emissions, with average reduction benefits of 8.70% ± 2.10% and 11.74% ± 2.95%, respectively. In conclusion, shore power adoption at the Port of Kaohsiung would greatly reduce air pollution in the port city, especially in residential areas, and be considered a sustainable solution to improving air quality and combating climate change.